Synthesis of Al7075/TiB2-Al2O3 In-Situ Hybrid Composite by Stir Casting Method - B. Sharifian; G. H. Borhani; E. Mohammad Sharifi (Journal of Advanced Materials in Engineering)
In this study, mechanically milled (MM) Al-24TiO2-20B2O3 powder in molten Al7075 matrix was used in order to fabricate in-situ TiB2 and Al2O3 reinforcements in Al7075 matrix. Differential thermal analysis (DTA) examination was adopted to find reaction temperature between milled Al, TiO2, and B2O3 powders. X-Ray Diffraction (XRD) patterns showed the existence of TiB2 and Al2O3 peaks (750 °C at Ar atmosphere) in MM powder. Scanning Electron Microscopy (SEM) results revealed the uniform distribution of TiO2 and B2O3 particles in the aluminum matrix. 6 wt.% MM powder was added to molten Al7075 at 750 °C. The molten Al7075/TiB2-Al2O3 composite was poured in copper mold. The stir casted composites were hot extruded at 465 °C with extrusion ratio of 6:1 and ram speed of 5 mm/s. The microstructures (optical microscopy and TEM) and mechanical properties (hardness and tensile testing) of samples were evaluated. TEM results showed that in-situ TiB2 nanoparticles were formed. The tensile strength of extruded Al7075/TiB2-Al2O3 composite was reached the value of 496 MPa. This result was around four times greater than that of the as cast Al7075 alloy.